2015
DOI: 10.1080/15384101.2015.1100774
|View full text |Cite
|
Sign up to set email alerts
|

p21WAF1 modulates drug-induced apoptosis and cell cycle arrest in B-cell precursor acute lymphoblastic leukemia

Abstract: Keywords: childhood acute lymphoblastic leukemia, etoposide, p21 WAF1 , patient derived xenograft models, terameprocol, vorinostat p21 WAF1 is a well-characterized mediator of cell cycle arrest and may also modulate chemotherapy-induced cell death. The role of p21 WAF1 in drug-induced cell cycle arrest and apoptosis of acute lymphoblastic leukemia (ALL) cells was investigated using p53-functional patient-derived xenografts (PDXs), in which p21 WAF1 was epigenetically silenced in T-cell ALL (T-ALL), but not in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
4
3
0
1
Order By: Relevance
“…SAHA treatment caused significant changes in proteins involved in both cell cycle and cell phenotype. We demonstrated that SAHA-loaded nanomicelles were able to up-regulate p21 and down-regulate p53 expression, consistent with the previous studies on the action of free SAHA on tumor growth inhibition by regulating the expression of these genes (Davies et al 2015;Ogata et al 2017). Detailed analysis of the effects of SAHA-loaded nanoparticles on EMT transition markers revealed a significant up-regulated E-cadherin expression, but with no affect N-cadherin expression.…”
Section: Discussionsupporting
confidence: 90%
“…SAHA treatment caused significant changes in proteins involved in both cell cycle and cell phenotype. We demonstrated that SAHA-loaded nanomicelles were able to up-regulate p21 and down-regulate p53 expression, consistent with the previous studies on the action of free SAHA on tumor growth inhibition by regulating the expression of these genes (Davies et al 2015;Ogata et al 2017). Detailed analysis of the effects of SAHA-loaded nanoparticles on EMT transition markers revealed a significant up-regulated E-cadherin expression, but with no affect N-cadherin expression.…”
Section: Discussionsupporting
confidence: 90%
“…Overexpression of p21 leads to the arrest of cells in the G1/G2 or S phases of the cell cycle [21,51], hence inhibiting the growth of tumor cells [52][53][54]. Here we demonstrated that SAHA-loaded nanomicelles were able to up-regulate p21 and down-regulate p53 expression, consistent with previous studies on the action of SAHA on tumor growth inhibition by regulating the expression of these genes [36,38,39,[55][56][57].…”
Section: Discussionsupporting
confidence: 91%
“…At the molecular level SAHA treatment caused signi cant changes in proteins involved in both cell cycle and cell phenotype. We demonstrated that SAHA-loaded nanomicelles were able to up-regulate p21 and down-regulate p53 expression, consistent with previous studies on the action of free SAHA on tumor growth inhibition by regulating the expression of these genes (Davies et al 2015;Ogata et al 2017).…”
Section: Discussionsupporting
confidence: 91%